Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s13046-020-01723-7
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antitumor interaction of valproic acid and simvastatin sensitizes prostate cancer to docetaxel by targeting CSCs compartment via YAP inhibition

Abstract: Background Despite the introduction of several novel therapeutic approaches that improved survival, metastatic castration-resistant prostate cancer (mCRPC) remains an incurable disease. Herein we report the synergistic antitumor interaction between two well-known drugs used for years in clinical practice, the antiepileptic agent with histone deacetylase inhibitory activity valproic acid and the cholesterol lowering agent simvastatin, in mCRPC models. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 82 publications
(115 reference statements)
0
22
0
Order By: Relevance
“…Taccioli et al identified that dasatinib and statins are an effective combined strategy for inhibiting YAP/TAZ in cancer cells by interrogating the Mutations and Drugs Portal (MDP) [ 298 ]. Iannelli et al demonstrated the ability of the valproic acid/simvastatin combination to sensitize metastatic castration-resistant prostate cancer cells to docetaxel and to revert docetaxel-resistance through mevalonate pathway/YAP axis modulation using both in vitro and in vivo models [ 299 ]. Adriamycin-based chemotherapy is the first-line treatment for osteosarcoma, but most patients will experience tumor recurrence and metastasis.…”
Section: Maximizing Efficacy and Addressing Shortcomings Of Conventional Cancer Therapymentioning
confidence: 99%
“…Taccioli et al identified that dasatinib and statins are an effective combined strategy for inhibiting YAP/TAZ in cancer cells by interrogating the Mutations and Drugs Portal (MDP) [ 298 ]. Iannelli et al demonstrated the ability of the valproic acid/simvastatin combination to sensitize metastatic castration-resistant prostate cancer cells to docetaxel and to revert docetaxel-resistance through mevalonate pathway/YAP axis modulation using both in vitro and in vivo models [ 299 ]. Adriamycin-based chemotherapy is the first-line treatment for osteosarcoma, but most patients will experience tumor recurrence and metastasis.…”
Section: Maximizing Efficacy and Addressing Shortcomings Of Conventional Cancer Therapymentioning
confidence: 99%
“…Gathering evidence demonstrated that synergistic antitumor effects of VPA and other therapeutic agents have been explored. The combination therapy of VPA and simvastatin sensitized prostate cancer cells via YAP inhibition (6). VPA and Arsenic Trioxide were verified to induce cell-cycle arrest at the G2/M phase and apoptotic cell death in lung cancer (88).…”
Section: Discussionmentioning
confidence: 94%
“…Valproic acid (VPA), one of the most common histone deacetylase inhibitors (HDACIs), is known as an anticonvulsant and mood-stabilizing drug clinically (5). Gathering evidence have manifested that VPA directly or synergistically exerted anti-tumor effects on various solid tumors (6,7). For instance, VPA suppressed gastric cancer cell proliferation and induced autophagy through HDAC1/PTEN/Akt signaling (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ianelli et al demonstrated the synergistic effects of simvastatin and valproic acid in sensitizing PCa to docletaxel and decreasing resistance rates. This combination method targets the CSCs by inhibiting the action of the Yes-associated protein (YAP) oncogene, a transcriptional regulator implicated in many cancers, including PCa [ 143 , 144 ]. Zhuang et al demonstrated that simvastatin acts to promote apoptosis via cholesterol depletion.…”
Section: Drug Repurposing In Prostate Cancermentioning
confidence: 99%